Pengaruh Sistem Informasi Keuangan dan Pengawasan Keuangan Terhadap Kinerja Pengelolaan Keuangan yang Dimediasi Komitmen Organisasi - Lusy Farina; Mahjus Ekananda; Fatia Fatimah (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
This research was conducted with the aim of knowing the effect of information systems and financial supervision on financial management performance, mediated by organizational commitment. The study population consisted of 240 UPBJJ-UT employees, and samples were taken using a purposive sampling technique with the Slovin formula, so that 155 respondents were obtained. The data analysis method used is Structural Equation Modeling-Partial Least Square (SEM-PLS) with the help of Smart-PLS version 3.0 software. The results of the study show that the financial information system has a positive, but not significant, effect on financial management performance. However, the financial information system has a positive and significant effect on organizational commitment. Meanwhile, financial supervision has a positive and significant effect on both financial management performance and organizational commitment. Finally, organizational commitment has a positive and significant effect on financial management performance. In addition, organizational commitment can also mediate information systems and financial supervision in influencing financial management performance. Therefore, the researcher recommends that the financial information system be revised periodically and aspects of financial supervision are further enhanced by authorizing the management of financial transactions. In addition, it is necessary to improve more intensive communication between management and employees to increase organizational commitment, so that financial performance can be further improved.